Legal Aspects of Abandoned Children: Legal Protection and Responsibilities of the Regional Government of Karawang Regency - Muhammad Rizky Hamzah; Wahyu Donri Tinambunan (Law and Justice, 2023)
As time goes by, there are increased cases of child neglect due to parents who want to run away from the burden of their responsibility to care for their children. Legal protection policies for abandoned children that have been applied so far tend to only add to their shortcomings without paying attention to the wider impact. This is because laws that are supposed to protect the basic rights of abandoned children are struggling with their own problems. This research uses research methods with the approach technique used is Normative Juridical. The approach used is a conceptual approach and a statue approach using primary, secondary and tertiary legal materials. Legal material analysis uses the nature of prescriptive analysis, which is to provide arguments for the results of research that has been done by providing prescriptions or judgments about right or wrong or what should be according to law against legal facts or events resulting from research. The results showed that the Constitution mandates the state to realize welfare as stated in the Articles in the Constitution. The function of the State in caring for abandoned children can be realized if the government as a policy maker and / or legislation must take sides and pay attention to various problems of abandoned children in Indonesia. The responsibility of the local government of Karawang Regency from the juridical aspect towards abandoned children relates to Regional Regulation Number 8 of 2012 concerning the Implementation of Social Welfare, which is carried out in two ways or steps, Coaching, and Advanced Development. The Karawang Regency Social Office collaborated with other elements